First record of the orchid bee genus Eufriesea Cockerell (Hymenoptera: Apidae: Euglossini) in the United States - Griswold, Terry; Herndon, James D.; Gonzalez, Victor H. (Zootaxa, 2015)
The orchid bee genus Eufriesea Cockerell is documented for the first time from the southwestern United States, extending its apparent range north well beyond its previous tropical/subtropical boundaries. Eufriesea coerulescens (Lepeletier de Saint Fargeau 1841) is recorded from the Guadalupe Mountains of western Texas and southeastern New Mexico, USA. Whether E. coerulescens is resident in the USA, or merely a vagrant from Mexico, remains unclear. Distinctive morphological traits shared with the holotype are enumerated and illustrated. In addition, observations that question the current species concept and distribution of E. coerulescens are provided.